HIGHER EDUCATION AS AN ENVIRONMENT FOR THE FORMATION OF THE HUMAN POTENTIAL OF THE TERRITORIES - TOMCHUK, Olesya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to the theoretical justification of the leading role of higher education as an environment for the formation of the human potential of the territories. The importance of human resources for the development of complex socio-economic systems in the conditions of post-industrial transformations of society is defined. The relationship between human potential and economic growth and social stability of territories is characterized. The socio-humanitarian and socio-economic goals of higher education are discovered, the importance of this system for the personal and professional growth of the population and its social mobility is emphasized. The influence of the higher education system on the formation of key structural elements of human potential: innovative, intellectual, labor, cultural and reproductive is determined. It was proven that the genesis, preservation, and development of all elements of the human potential of the territory directly depend on the effectiveness of the functioning of the higher education system. It was established that regions where there is an opportunity to obtain high-quality higher education systematically attract talented youth and accumulate human potential more efficiently. The main challenges (both traditional for this field and those caused by the war) faced by the Ukrainian higher school today as an environment for the formation of the human potential of the territories are outlined. It was noted that the Industry 4.0 will be a basis of the post-war reconstruction of Ukraine with its inherent reliance on high-tech sectors of the economy, for which human potential with appropriate qualimetric characteristics will be necessary. A set of priority directions for the development of the higher education system as an environment for the formation of human potential is proposed. Conclusions were made regarding the importance of systematic and consistent development of higher education as a prerequisite for ensuring the effective formation of the human potential of the territories.
Keywords: human potential; formation of human potential of territories; higher education; strategy; development of higher education; institution of higher education